SOCIAL SELF-DETERMINATION OF MAN IN THE INFIRMATION SOCIETY - Автомонова, Т. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problems of self-determination in the social dimension of man’s life are considered in the comparative profile of the cultural directions and social-economical conditions of the modern and industrial ages as a specific manifestation of man’s nature spirit, which stipulates social life.